2016
DOI: 10.1074/jbc.m116.730432
|View full text |Cite
|
Sign up to set email alerts
|

Human Naa50 Protein Displays Broad Substrate Specificity for Amino-terminal Acetylation

Abstract: Amino-terminal acetylation is a critical co-translational modification of the newly synthesized proteins in a eukaryotic cell carried out by six amino-terminal acetyltransferases (NATs). All NATs contain at least one catalytic subunit, and some contain one or two additional auxiliary subunits. For example, NatE is a complex of Naa10, Naa50, and Naa15 (auxiliary). In the present study, the crystal structure of human Naa50 suggested the presence of CoA and acetylated tetrapeptide (AcMMXX) that have co-purified w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Our work demonstrates that NAA50 is catalytically active in the reference plant Arabidopsis. AtNAA50 has a broad substrate specificity, which substantially overlaps with the substrate specificity of HsNAA50 (Van Damme et al, 2011;Reddi et al, 2016). Although we detect a preference of AtNAA50 for iMet followed by Lys (K), Asn (N), Gln (Q), and Thr (T) in the second position (Fig.…”
Section: Discussion Naa50 Activity Is Functionally Conserved Between mentioning
confidence: 62%
“…Our work demonstrates that NAA50 is catalytically active in the reference plant Arabidopsis. AtNAA50 has a broad substrate specificity, which substantially overlaps with the substrate specificity of HsNAA50 (Van Damme et al, 2011;Reddi et al, 2016). Although we detect a preference of AtNAA50 for iMet followed by Lys (K), Asn (N), Gln (Q), and Thr (T) in the second position (Fig.…”
Section: Discussion Naa50 Activity Is Functionally Conserved Between mentioning
confidence: 62%
“…In higher eukaryotes, Naa50 and Huntington yeast two-hybrid protein K (HypK) have been identified to associate with NatA. The catalytic subunit Naa50 acetylates substrates different from NatA and in complex with NatA forms NatE 1 13 24 25 26 27 28 29 . Interestingly, the HypK, which was first identified as an interaction partner of Huntingtin 30 31 , is associated with the NatA complex 32 .…”
mentioning
confidence: 99%
“…The NTA activity of human Naa50 has been demonstrated previously (Liszczak et al, 2011;Van Damme et al, 2011;Reddi et al, 2016;Evjenth et al, 2009). In the companion paper from Armbruster et al (2020), Arabidopsis NAA50 is shown to have NTA activity in vitro on synthetic peptides, and in vivo when expressed in E. coli.…”
Section: Naa50 Is Required For Growth and The Suppression Of Stress Rmentioning
confidence: 87%